Strategi Manajemen Konflik Untuk Meningkatan Kualitas Kerja Dalam Organisasi - Djoko Hananto; Adelin Sri Wahyuningrum; Maulingga Silmi Kafah; Raihan Ardani; Muhamad Rohid Al Candra (Program Studi Ekonomi Syariah Fakultas Agama Islam Universitas Pahlawan Tuanku Tambusai, 2024)
Conflict management was an important element in the organization to ensure a harmonious and productive work environment. Poorly managed conflicts could disrupt team performance, decrease employee motivation, and damage organizational culture. The study aimed to explore effective conflict management strategies to enhance work quality within the organization. Through literature review and case studies in several companies, it was found that collaborative approaches, open communication training, and conflict management played a key role in minimizing the negative impacts of conflicts. The method used in this research was qualitative with a narrative problem-solving approach. Implementing these strategies not only helped resolve conflicts but also encouraged innovation, strengthened employee relationships, and improved overall job satisfaction. Therefore, the research findings indicated that effective conflict management was crucial in achieving high-quality work and long-term organizational success.